Psychosocial status and sleep quality of the patients with idiopathic intracranial hypertension (Annals of Medical Research, 2021)
Aim: To investigate the level of depression and anxiety measures, sleep quality indexes and to measure the quality of life in patients with idiopathic intracranial hypertension (IIH).Material and Methods: Using a case-control cross-sectional design, 17 patients with IIH were compared with 16 healthy controls of similar age and gender. Patients were assessed for aggression, depression, and anxiety using the Buss-Perry Aggression Questionnaire, the Beck Depression Inventory (BDI) and the Beck Anxiety Inventory (BAI). The quality of life levels was assessed by the 36-Item Short-Form Health Survey (SF-36). The sleep quality of the individuals was evaluated using the Pittsburgh Sleep Quality Index (PSQI), STOP questionnaire, Epworth sleepiness scale (ESS). Results: The scores of BDI and the BAI were higher in the patient group, however, there were no significant differences (p=0.36, p=0.14, respectively). The results of the questionnaires related to sleep quality including PSQI, STOP questionnaire and ESS were worse in the patient group; however, no statistical differences were found (p=0.65, p=0.14, p=0.33, respectively). All of the eight domains of the SF-36 were also compared between the groups which revealed that the scores of all of the subitems were lower in the patient group. However, the statistical difference was only found in the subitem of ‘energy/fatigue’ (p = 0.02). Conclusion: Our study results provide encouraging conclusions remarking the worse psychosocial status in patients with IIH. The relevance and clinical impact of psychological status and quality of life in patients with IIH need to be investigated in future large-scale studies. Besides, the low energy/fatigue measures in IIH patients and its temporal course after the initiation of IIH treatment may constitute crucial topics to be investigated in these studies.
Keywords: Idiopathic intracranial hypertension; psychological status; quality of life; sleep quality; energy and fatigue